Human activities altered the enrichment patterns of microplastics in mangrove blue carbon ecosystem in the semi-enclosed Zhanjiang Bay, China - Zhang, Peng; Zhao, Wei; Zhang, Jibiao; Gao, Yeqin; Wang, Shujia; Jian, Qiying (Frontiers in Marine Science, 2024)
Mangroves, as part of the blue carbon ecosystem, are considered ‘potential sinks’ for microplastics (MPs) in the land-ocean interface zones. However, there is limited understanding of enrichment patterns of MPs in mangrove blue carbon ecosystem, particularly in relation to human activities. This study explored the abundance, composition, and diversity of MPs in mangrove and non-mangrove sediments in Zhanjiang Bay (ZJB) to investigate the effects of human activities on MPs enrichment patterns in the blue carbon system. The results showed that MPs were widely prevalent in all sediment samples, and the abundance of MPs was significantly higher in all mangrove sediments than in non-mangrove sediments (P < 0.05). Furthermore, the average abundance of MPs was found to be 263.67 ± 85.25 items/kg in non-mangrove sediment samples, whereas in mangrove sediment samples, it was 618.17 ± 71.75 items/kg. The average abundance of MPs in mangroves was about 1.6 times higher than that in non-mangroves, indicating that mangroves have an interception effect on MPs, and human activities are the key factor leading to the difference in MPs enrichment patterns between mangroves and non-mangroves. Furthermore, the predominant MPs shapes in both mangroves and non-mangroves are fragments, with multicolor and green being the most common colors and most MPs sizes ranging between 100 and 330 µm. Besides, there was no significant relationship found between MPs abundance and particulate organic carbon (P > 0.05), indicating that MPs pollution didn’t significantly alter the natural POC pool in ZJB. Overall, this study provided important baseline information on MPs pollution in the mangrove blue carbon ecosystems in ZJB, which was implications for future mitigation of MPs pollution and the management of mangrove ecosystem.